Training curriculum for European thoracic surgeons: a joint initiative of the European Society of Thoracic Surgeons and the European Respiratory Society - (:unkn) unknown (OXFORD UNIV PRESS INC, 2020)
Because of the differing definitions of the margins of thoracic surgery as a specialty and the variability in the training curricula among European countries, the European Society of Thoracic Surgeons formed a task force to elaborate a consensual proposal. The first step comprised creating a harmonized syllabus that was completed and published in 2018. This publication presents a proposal for a curriculum upon which the task force and the external expert reviewers have agreed. The curriculum was developed by the task force: each module and item describe the expected level of knowledge, skills and attitudes to be attained by the participants; learning opportunities, assessment tools and minimal clinical exposures have been defined as well. Competence in terms of non-technical skills has been defined for each module according to the CanMEDS (http://www.royalcollege.ca/rcsite/canmeds/canmeds-framework-e) glossary. The different modules were subsequently submitted to an internal and an external review process and re-edited accordingly before final validation. The authors hope that this document will serve as a roadmap for both thoracic surgical trainees and mentors. It should further guide continuous professional development. However, evolving scientific and technological advances are expected to modify the diagnosis and treatment of diseases and disorders in the future and hence will mandate periodical revisions of the document.
Keywords: Thoracic surgery; Education; HERMES; SYLLABUS; SKILLS; RECOMMENDATIONS